2014
DOI: 10.1039/c3cc48468h
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise addition of difluorocarbene to a transition metal centre

Abstract: The Ruppert-Prakash reagent (Me3SiCF3) is used to introduce difluorocarbene (CF2) and tetrafluoroethylene (TFE) ligands to cobalt(I) metal centres, whereby the TFE ligand is generated via [2+1] cycloaddition between [Co]=CF2 and CF2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…During the investigation, we noticed that TFE was normally formed as a side product (see the Supporting Information) . In 2014, Baker and co‐workers observed that a mixture of TMSCF 3 and NaI in THF could produce TFE and thus proposed that the thus‐formed TFE could directly add to cobalt complexes . Although this TFE generation method is very intriguing owing to its mildness, it is still unclear whether it is synthetically useful as gaseous TMSF is also present as a byproduct.…”
Section: Methodsmentioning
confidence: 99%
“…During the investigation, we noticed that TFE was normally formed as a side product (see the Supporting Information) . In 2014, Baker and co‐workers observed that a mixture of TMSCF 3 and NaI in THF could produce TFE and thus proposed that the thus‐formed TFE could directly add to cobalt complexes . Although this TFE generation method is very intriguing owing to its mildness, it is still unclear whether it is synthetically useful as gaseous TMSF is also present as a byproduct.…”
Section: Methodsmentioning
confidence: 99%
“…During the investigation, we noticed that TFE was normally formed as a side product (see the Supporting Information) . In 2014, Baker and co‐workers observed that a mixture of TMSCF 3 and NaI in THF could produce TFE and thus proposed that the thus‐formed TFE could directly add to cobalt complexes . Although this TFE generation method is very intriguing owing to its mildness, it is still unclear whether it is synthetically useful as gaseous TMSF is also present as a byproduct.…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, Baker and co‐workers observed that a mixture of TMSCF 3 and NaI in THF could produce TFE and thus proposed that the thus‐formed TFE could directly add to cobalt complexes . Although this TFE generation method is very intriguing owing to its mildness, it is still unclear whether it is synthetically useful as gaseous TMSF is also present as a byproduct. Herein, we report the synthetic application of readily available TMSCF 3 as a convenient TFE source for per‐ and polyfluoroalkylation reactions.…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28][29][30] In 2011, our group, in collaboration with the Prakash group, revealed that TMSCF 3 is a good diuorocarbene precursor, which can be used in the [2 + 1] cycloaddition reaction with alkenes and alkynes. 31 Recently, our group reported that diuorocarbene generated from TMSCF 3 could undergo dimerization to give tetra-uoroethene (TFE), 32,33 which can be used for a variety of transformations. 33 Very recently, our group demonstrated that, by using TMSCF 3 as the diuoromethylene source, controllable CF 2 -insertion into CuCF 3 to generate CuCF 2 CF 3 could be realized.…”
Section: Introductionmentioning
confidence: 99%